Kesetaraan Gender dalam Sastra Pesantren (Kajian terhadap Kitab Syi’ir Laki Rabi) - Mohammad Muzakka Mussaif (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
Gender issues are discussed in many literary works, whether they are foreign literature, Indonesian literature, or regional literature. Gender issues also appear in religious literature and or pesantren literature. Most of the gender issues that arise in religious literature and or pesantren are issues of gender bias or gender imbalances that are confirmed by the arguments of the Qur'an and the hadith of the Prophet. However, in the literature study of pesantren with the approach of feminist literary criticism of the Sy'ir Laki Rabi by Haji Zakaria did not show any gender bias. The results show that the gender issues raised in this poem are not loaded with gender bias. This work, though, speaks of domestic life, but it emphasizes the duties, duties, and rights of husband and wife.